2002
DOI: 10.1002/bit.10473
|View full text |Cite
|
Sign up to set email alerts
|

Study of caspase inhibitors for limiting death in mammalian cell culture

Abstract: Apoptosis in mammalian cell culture is associated with decreased bioproduct yields and can be inhibited through altering the intracellular signaling pathways mediating programmed cell death. In this study, we evaluated the capacity to inhibit caspases to maintain high viable cell numbers in CHO and 293 cultures. Two genetic caspase inhibitors, XIAP and CrmA, were examined along with a mutant of each, XIAP-BIR123NC, which contains three BIR domains but lacks the RING finger, and CrmA-DQMD, which has CrmA's pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 89 publications
0
48
1
Order By: Relevance
“…3) suggesting that C 3 LP activation is necessary for cell death. Indeed, when an irreversible inhibitor of caspase, Z-VAD-fmk (carbobenzoxy-valyl-alanyl-aspartyl (b-methyl ester)-fluoro-methyl ketone) (Kohler et al, 2002;Sauerwald et al, 2003), was applied to cells under shear stress at 8 h and C 3 LP activity measured at 10 h, the activity was reduced to levels similar to that of control cells (Fig. 4).…”
Section: Caspase-3-like Protease (C 3 Lp) Is Activated By Shear Stresmentioning
confidence: 65%
See 1 more Smart Citation
“…3) suggesting that C 3 LP activation is necessary for cell death. Indeed, when an irreversible inhibitor of caspase, Z-VAD-fmk (carbobenzoxy-valyl-alanyl-aspartyl (b-methyl ester)-fluoro-methyl ketone) (Kohler et al, 2002;Sauerwald et al, 2003), was applied to cells under shear stress at 8 h and C 3 LP activity measured at 10 h, the activity was reduced to levels similar to that of control cells (Fig. 4).…”
Section: Caspase-3-like Protease (C 3 Lp) Is Activated By Shear Stresmentioning
confidence: 65%
“…Five of these, caspases 3, 6, 7, 8, and 9, are actively involved in the caspase cascade of different forms of apoptosis (Sauerwald et al, 2003). Of these caspases, the presence and involvement of caspase-3-like activity has been previously demonstrated in Xanthomonas campestris (Gautam and Sharma, 2002a).…”
Section: Caspase-3-like Protease (C 3 Lp) Is Activated By Shear Stresmentioning
confidence: 97%
“…Up to now, there have been many approaches to overcome apoptotic cell death during batch cultures by (1) genetically modifying important genes in cell growth, 8,[10][11][12][13][14][15][16][17][18] (2) supplementing essential nutrients, [19][20][21] or (3) adding chemical inhibitors. 22,23 We address each of these approaches below.…”
mentioning
confidence: 99%
“…Mastrangelo et al (2000) showed that CHO-bcl-xL and BHK-bcl-2 had a lifespan that was double that of the parental cell line postinfection with alphavirus and recombinant CAT showed a twofold increase in production in cell lines over-expressing bcl-2 and bcl-xL, however IL-12 production was greater in CHO-bcl-xL and CHO-bcl-2 whilst reduced in BHK-bcl-xL and BHK-bcl-2. The same group later showed that apoptosis induction by sindbis virus was attenuated in CHO and HEK293 cells using chemical caspase inhibitors and over-expression of XIAP; an anti-apoptosis gene that targets caspases (Sauerwald et al, 2002(Sauerwald et al, , 2003. Vaccina virus induced cell death was limited by over-expression of bcl-2 in immature B-lymphocytes (Baixeras et al, 1998).…”
Section: Introductionmentioning
confidence: 93%